IMPROVING STUDENT'S ANALYSIS SKILL THROUGH THE IMPLEMENTATION OF SEARCH, SOLVE, CREATE, AND SHARE (SSCS) LEARNING MODEL IN MAIN MATERIALS OF LIVING THINGS CLASSIFICATION FOR VII / A GRADE STUDENTS OF UPT SMP NEGERI 10 GRESIK - Rahmat Amin (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The method of learning SSCS (Search Solve Create and Share) is a learning method that uses a problem solving approach designed to develop critical thinking skills and improve understanding of the concept of science. The use of this model in classroom learning can provide assistance to teachers to develop student creativity in problem-oriented learning. Researchers use the method of learning SSCS (Search Solve Create and Share) because this method is practical, effective, and simple to use. At the search stage students ask inquiry questions about topics they like to investigate. Furthermore, at the solve stage students create a design for the design to be used for the investigation. After conducting an investigation students perform analysis and interpret the data obtained. The student then determines the way to communicate his findings, and this stage is the create stage. The last stage in SSCS learning method is share. At this stage students share or provide results and evaluations of the investigations it undertakes. It is expected that the use of SSCS (Search Solve Create and Share) method can improve the learning outcomes of science students of grade VII UPT SMP Negeri 10 Gresik. Implementation of Search, Solve, Create, and Share (SSCS) learning model can improve students' analysis ability on the subject matter of Classification of Beings of VII / 1 students of UPT SMP Negeri 10 Gresik in the academic year 2019/2020. This can be seen based on the results of the implementation of the action in cycle I, namely the achievement of students with high analysis ability category by 57%. and increased to 73% in cycle II. Implementation of Search, Solve, Create, and Share (SSCS) learning model can improve students' learning achievement on the subject matter of Classification of Beings of VII / 1 students of UPT SMP Negeri 10 Gresik in the academic year 2019/2020. The quality of student learning outcomes in this study includes aspects of